2019
DOI: 10.1051/0004-6361/201935745
|View full text |Cite
|
Sign up to set email alerts
|

X-shooter spectroscopy of young stars with disks

Abstract: Context. Measurements of the fraction of disk-bearing stars in clusters as a function of age indicate protoplanetary disk lifetimes ≲10 Myr. However, our knowledge of the time evolution of mass accretion in young stars over the disk lifespans is subject to many uncertainties, especially at the lowest stellar masses (M⋆). Aims. We investigate ongoing accretion activity in young stars in the TW Hydrae association (TWA). The age of the association (∼8–10 Myr) renders it an ideal target for probing the final stage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 129 publications
(265 reference statements)
8
45
2
Order By: Relevance
“…Overall, we do not see noticeable differences between the accretion rates measured in the 13 targets in the Orion OB1 and σ-Ori regions with respect to what is observed in other young star-forming regions with similar techniques. This result is in agreement with the findings of Manara et al (2020), Venuti et al (2019), Rugel et al (2018), andIngleby et al (2014), among others, who found that the accretion rates of still accreting objects at ages of >3−5 Myr are still comparable to the accretion rates of younger stars. However, this result is still puzzling as these high accretion rates are difficult to reconcile with the current framework to describe disk evolution (e.g., Ingleby et al 2014;Manara et al 2020).…”
Section: Accretion Properties Of Young Low-mass Starssupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, we do not see noticeable differences between the accretion rates measured in the 13 targets in the Orion OB1 and σ-Ori regions with respect to what is observed in other young star-forming regions with similar techniques. This result is in agreement with the findings of Manara et al (2020), Venuti et al (2019), Rugel et al (2018), andIngleby et al (2014), among others, who found that the accretion rates of still accreting objects at ages of >3−5 Myr are still comparable to the accretion rates of younger stars. However, this result is still puzzling as these high accretion rates are difficult to reconcile with the current framework to describe disk evolution (e.g., Ingleby et al 2014;Manara et al 2020).…”
Section: Accretion Properties Of Young Low-mass Starssupporting
confidence: 93%
“…It is only by observing large samples of young stars and probing wide ranges of age and mass that we can gain access to a sufficient set of statistics to aid in the understanding of both processes. Spectroscopic surveys of young stars in different star-forming regions have shown that the mass accretion rates onto the central star (Ṁ acc ) slowly decrease with isochronal ages, possibly in accordance with viscous evolution models (e.g., Hartmann et al 1998;Sicilia-Aguilar et al 2010;Antoniucci et al 2014), although high accretion rates are still observed at ages of >5−10 Myr A&A 650, A196 (2021) (e.g., Ingleby et al 2014;Frasca et al 2015;Rugel et al 2018;Venuti et al 2019;Manara et al 2020). The empirical measurement of the steep dependence ofṀ acc on the stellar mass (M ) (Hillenbrand et al 1992;Muzerolle et al 2003;Calvet et al 2004;Mohanty et al 2005;Natta et al 2006;Manara et al 2012Manara et al , 2016aManara et al , 2017aAlcalá et al 2014Alcalá et al , 2017Venuti et al 2014) may be the consequence of a single dominant phenomenon or a mix of many, such as, initial conditions followed by viscous evolution (e.g., Alexander et al 2006;Dullemond et al 2006), an imprint of internal photoevaporation (e.g., Ercolano et al 2014), different accretion regimes at different stellar masses (e.g., Mohanty et al 2005;Hartmann et al 2006), environmental effects (e.g., Padoan et al 2005), or self-gravity in the disk (e.g., Vorobyov & Basu 2009;DeSouza & Basu 2017).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…We note that very recently Manara et al (2020) found similarly high accretion rates reported for ET Cha around several members of the ∼5 Myr Upper Scorpius region (see also Ingleby et al 2014;Venuti et al 2019 for Orion OB1 and TWA). The mass estimate in this case was based on the dust.…”
Section: Interaction With the Circumstellar Disksupporting
confidence: 77%
“…The detection of strong accretors at later ages, and the connected hint of a lack of a general decrease of accretion rates with time when the targeted stars are still hosting a disk, has already been observed in different older star-forming regions: the nearby loose associations TWA (Venuti et al 2019) and η-Cha (Rugel et al 2018), the more distant γ-Velorum cluster (Frasca et al 2015), Orion OB1b and Orion OB1a associations (Ingleby et al 2014), and even the very massive regions like NGC3603 or 30 Doradus (De Marchi et al 2017). Individual targets have also been found to be still accreting at age >20 Myr (e.g., Mamajek et al 2002;Zuckerman et al 2014;Murphy et al 2018;Lee et al 2020).…”
Section: Does the Mass Accretion Rate Decrease With Time?mentioning
confidence: 87%